Stem cells, a novel treatment for periodontitis. - López Conde, Yeilyn de la Caridad; Cabello Rojo, Ailed; Mérida Argüéz, Daniela; Martín Pinto, Mildred; Fernández Cámara, Jorge (Revista 16 de abril, 2017)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The periodontitis is the fundamental cause of the tooth failure from 35 years old and its prevalence is very high. A lot of treatments have been used but without doubt one of the most newfangled is the use of mother cells. The knowledge which can be gotten in Molecular and Cellular Biology subject was the motivation to do this bibliographyc review with the objective to describe mother cells´s characteristics and its use in the periodontitis treatment, that´s why 24 bibliographyc were reviewed. Because of mother cells their capacity of dividing indefinitely, are fundamentals in the tissues regeneration, that´s why they are used in the treatment of this and others diseases with effects much more promising every time. The treatment with mother cells guaranteethe impaired tissues, the fast disappearance of after-surgery inflammations and durability of the oral health in patients with chronic periodontitis.